2007
DOI: 10.1152/ajpendo.00101.2007
|View full text |Cite
|
Sign up to set email alerts
|

Ciliated epithelial-specific and regional-specific expression and regulation of the estrogen receptor-β2 in the fallopian tubes of immature rats: a possible mechanism for estrogen-mediated transport process in vivo

Abstract: eral ER␤ isoforms have been identified in human and rodent tissues, but it is unclear whether each isoform has distinctly different cellular targeting characteristics and physiological functions. We have investigated the intracellular localization and regulatory patterns for ER␤ isoforms in rat fallopian tubes. Western blot analysis reveals that two ER␤ isoforms corresponding to ER␤1 and ER␤2 are expressed in rat fallopian tubes. However, ER␤2 is the predominant form of ER␤ in this tissue. High-resolution conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 75 publications
1
43
1
Order By: Relevance
“…This may be the case in the oviduct, where ERb is also expressed in epithelial cell cilia. Although the function of this ER in the oviduct relative to CBF is not defined, it has recently been shown that, in the lung, ERb mediates a rapid, nongenomic effect to speed CBF (47,48). In our studies, we did not find that E2 alone directly affects CBF when assayed at 24 hours; however, E2 blocked P4-mediated CBF inhibition at that time, emphasizing the importance of hormone balance.…”
Section: Discussioncontrasting
confidence: 74%
“…This may be the case in the oviduct, where ERb is also expressed in epithelial cell cilia. Although the function of this ER in the oviduct relative to CBF is not defined, it has recently been shown that, in the lung, ERb mediates a rapid, nongenomic effect to speed CBF (47,48). In our studies, we did not find that E2 alone directly affects CBF when assayed at 24 hours; however, E2 blocked P4-mediated CBF inhibition at that time, emphasizing the importance of hormone balance.…”
Section: Discussioncontrasting
confidence: 74%
“…Furthermore, truncated forms of both ER␣ and ER␤ have been identified in many estrogen target tissues and cell types (2,3,32,42), suggesting that the tissue/cell-specific responses to estrogen resulting in the divergence of biological function may at least in part be due to differences in the differential expression and regulation of ER␣/␤ isoforms. Recently, we have demonstrated the presence of ER␤ isoforms specifically in the ciliated epithelial cells of rat fallopian tube (56). Although the molecular mechanisms of ER␤ function in the fallopian tube still need to be clearly elucidated, our data suggest that ER␤ is involved in the estrogen-mediated regulation of calcium-dependent ciliated beating (56).…”
mentioning
confidence: 68%
“…Recently, we have demonstrated the presence of ER␤ isoforms specifically in the ciliated epithelial cells of rat fallopian tube (56). Although the molecular mechanisms of ER␤ function in the fallopian tube still need to be clearly elucidated, our data suggest that ER␤ is involved in the estrogen-mediated regulation of calcium-dependent ciliated beating (56). In contrast to ER␤, it has been postulated that ER␣ gene common polymorphisms in humans have been associated with female infertility (7), and ER␣ serves as a dominant regulator in fallopian tube development (44).…”
mentioning
confidence: 99%
“…The obtained value of the band intensity of each protein (i.e. MT1, p34Cdk1 or cyclin B) was then normalized by the intensity of b-actin and expressed as relative densitometric units (a ratio of the band intensity of the protein to b-actin for each sample) (Shao et al 2007). MeanGS.E.M.…”
Section: Discussionmentioning
confidence: 99%